Role of weather parameters on seasonal abundance of insects in a mangobased agroforestry in Bangladesh, with particular reference to mango hopper - Namni, S; Amin, MR; Miah, MRU; Rahman, MF; Suh, SJ (Bangladesh Journal of Agricultural Research, 2017)
Weekly sweeping was done by sweep net in order to collect insects to study the effect of weather parameters on the seasonal abundance of total insect species as well as mango hopper population in a mango-based agroforestry in Bangladesh during January to June 2013. The total insect species abundance was the highest during April to May, following the flushing of inflorescence and fruit set. At that time temperature and relative humidity were comparatively higher and there was rainfall. Mango hopper population was the highest in May and synchronized to fruit set. The abundance of total insect species and mango hopper population showed significant positive correlation with temperature, and relative humidity, while significant negative correlation with light intensity and non-significant positive correlation with rainfall. Multiple linear regression equation based on weather parameters revealed 59.2% and 61.7% role on population build up of total insect species and mango hopper, respectively. Temperature was found to be the most important effect which individually contributed 31.3% on population abundance of total insect species and 29.9% on mango hopper. Bangladesh J. Agril. Res. 42(2): 197-205, June 2017